Earth abundant iron-rich N-doped graphene based spacer and cavity materials for surface plasmon-coupled emission enhancements - Srinivasan, Venkatesh; Vernekar, Dnyanesh; Jaiswal, Garima; Jagadeesan, Dinesh; Ramamurthy, Sai Sathish (ACS Applied Materials & Interfaces, 2016)
We demonstrate for the first time the use of Fe based nanoparticles on N-doped graphene as spacer and cavity materials and study their plasmonic effect on the spontaneous emission of a radiating dipole. Fe-C-MF was produced by pyrolizing FeOOH and melamine formaldehyde precursor on graphene, while Fe-C-PH was produced by pyrolizing the Fe-phenanthroline complex on graphene. The use of the Fe-C-MF composite consisting of Fe-rich crystalline phases supported on N-doped graphene presented a spacer material with 116-fold fluorescence enhancements. On the other hand, the Fe-C-PH/Ag based cavity resulted in an 82-fold enhancement in Surface Plasmon-Coupled Emission (SPCE), with high directionality and polarization of Rhodamine 6G (Rh6G) emission owing to Casimir and Purcell effects. The use of a mobile phone as a cost-effective fluorescence detection device in the present work opens up a flexible perspective for the study of different nanomaterials as tunable substrates in cavity mode and spacer applications.
Keywords: Casimir effect; fluorescence enhancements; iron carbides; N-doped graphene; Purcell factor; surface plasmon-coupled emission